Isolation, Identification, Antimicrobial Activities, and Application of the Crude Pigmented Extract of Soil Actinobacteria in Handicraft and Painting - Urtgam, Sittichai; Puengtang, Chaowalit; Nakthong, Muthita; Sa-ngat, Pijittra; Sirisan , Prattana; Sumpradit , Tawatchai; Thurnkul , Naruemol (Bogor Agricultural University, Indonesia, 2026)
A total of 21 actinobacterial strains were isolated from soils in Thailand. The selected strains were applied for pigment extraction before handicraft and painting application. Based on the color tones, 4 actinobacterial strains, namely B3 (yellow), B8 (violet), F4 (brown), and F9 (pink), were selected. Their antimicrobial activities against pathogenic bacteria and molds, including Escherichia coli PSRU-01, Staphylococcus aureus PSRU-01, Colletotrichum sp. NPJM -01, and Fusarium sp. PSRU-01 were tested using the agar well and the poisoned food techniques. Phylogenetic identification was analyzed on the basis of partial 16S rDNA sequence comparison for species delineation. They closed Streptomyces tendae 99.73% (B3), Streptomyces muensis 99.52% (B8), Streptomyces ardesiacus 99.38% (F4), and Streptomyces iakyrus 99.59% (F9). These strains were evaluated for their potential as colorants in handicraft clay and painting colors. Streptomyces pigment may be a naturally produced and eco-friendly alternative for handicraft and painting applications.